How Betrayal and Mental Struggle Are Represented through Lyrics: Ideational Metafunction Study of Yebba’s My Mind - Muhammad Dzimar; Syafhika Rosilatu Zahra; Dewi Puspitasari (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
Language is very important because people use it to share their thoughts and feelings. This study talks about how a singer named Yebba shows her feelings of betrayal and sadness in her song My Mind. Many people listen to songs, but not many understand how the words in a song can show deep emotions. The purpose of this study is to find out how Yebba uses language to express her mental struggle and broken heart. The writers used a qualitative method, which means studying the song’s lyrics carefully to find the meaning behind the words. The research used Halliday’s Systemic Functional Linguistics, especially the part called transitivity, which looks at actions, feelings, and people in sentences. The results show that most of the sentences use material processes, which describe real actions like closing the door or leaving. There are also mental processes that show what the singer thinks and feels, and relational processes that describe what something is like. The song uses language to show both outside actions and inner emotions. In the end, this study shows that Yebba’s My Mind tells the story of betrayal and emotional pain through the way the words are used. It also helps us understand how songs can use simple language to show deep feelings. The study suggests that other researchers can use this method to study different songs and learn how singers express their emotions through words.